STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BURSA KERJA KHUSUS (BKK) STUDI DESKRIPTIF DI SMK NEGERI 2 CIMAHI (Jurnal Tata Kelola Pendidikan, 2020)
This research was titled "School principal's leadership strategy in developing a special jobmarket (BKK) descriptive study at SMK Negeri 2 Cimahi". This study aims to determinethe principal's leadership strategy in developing BKK. This study uses a descriptive methodof qualitative approach. The data collection technique used is interviews anddocumentation studies. In carrying out the duties and functions of the BKK SMK Negeri 2Cimahi refers to the decision of the Director General of Development and Placement ofDomestic Workers Number: Kep-131 / DPPTKDN / XI / 2004 concerning TechnicalGuidelines for Special Peterinary Exchange. In carrying out his duties of the principalreferring to the function of the Goldlim (Educator, Manager, Administrator, Supervisor,Leader, Innovator, Motivator) plus the Leader of Entrepreneur. The role of edification ofleadership through the Educator function, namely facilitating the BKK coordinator toattend the technical guidance of BKK management and attending a meeting between BKKChairperson, in addition to making a cooperation MoU with the company, coordinatingwith the Cimahi City Manpower Office and Ministry In the implementation there areseveral obstacles, including the lack of staff in BKK, policies that are not in one direction,parental permission, there are still graduates who are not ready to work, the existence ofcompanies that want to recruit do not match the majors, the limitations of the school inaccessing employment information, and age The recommendations for schools, especiallyto develop BKK, namely schools need to re-analyt the need for employees, especially forBKK staff, the school needs to convince students' parents that the Vocational School aimsto create individuals who are ready to plunge into the business world / industry and havebeen equipped with certain competencies. Then the school can create a culture that issimilar to the business of the business world / industrial world to improve the readiness ofstudents to work.
Keywords: Leadership strategy; Special job market